Avaliação de Desempenho no Georreferenciamento de Imagens do Sensor HR CCD (High Resolution Charge-Coupled Device) do Satélite CBERS-1 - ZANARDI, RAFAEL PEREIRA; ROLIM, SILVIA BEATRIZ ALVES; BIELENKI JÚNIOR, CLÁUDIO; DE ALMEIDA, CARLOS ALUISIO MESQUITA (Pesquisas em Geociências, 2005)
<!– .p text-align: justify; –> In this work it was analyzed the validation of CBERS-1 (China and Brazillian Earth Resourses Satellite) data related to qualitative and quantitative parameters that define the precision of its georeferencing. A topographical survey was carried out for the acquisition of ground control points spatially well distributed in the study area, employing differential GPS, aiming at the georeferencing of the image. Tests with different numbers of sampling points and several methods of Geometric Transformation and Resampling were made during the georeferencing. These results were statistically analyzed to determine the best method to georeference CBERS-1 images. It was verified that the first-degree polinomial transformation with nearest neighborhood resampling presented the best result, showing a precision of 18,52m.